A descriptive study: AI integration among pre-service PPG graduates in the era of Society 5.0 - Riska Nur Rohmah; Latifah Hanum (Jurnal Ilmiah Profesi Guru (JIPG), 2026)
Teachers are not limited to technical skills in using technology, but also being able to process information well to support the learning process in the era of society 5.0. The objective of this study is to descriptively analyze the integration of AI by pre-service PPG graduates as an effort to prepare professional teachers in the Society 5.0 era. The approach used in this research is descriptive quantitative method, namely by collecting data obtained from the answers of respondents who have filled out a closed questionnaire. The questionnaire used contained 25 questions with a Likert scale. The questionnaire results were processed using frequency distribution analysis to determine the percentage of responses. The subjects of this study were 98 participants who had graduated from the Pre-Service PPG program at several universities spread across Indonesia and had been accredited by the Ministry of Education and Culture. The results found in this study, namely: 1) pre-service PPG teacher candidates have been able to master digital technology, especially in the learning they do; 2) pre-service PPG teacher candidates have good digital literacy, especially to support the implementation of learning; 3) pre-service PPG teacher candidates have conducted humanism-based learning; 4) pre-service PPG teacher candidates recognize the importance of self-development in the current digital era; and 5) pre-service PPG teacher candidates have understood the importance of data-based evaluation. Furthermore, this research provides important input for PPG providers to improve the technology curriculum for future teachers in the Society 5.0 era. Studi deskriptif: Integrasi AI pada lulusan PPG Prajabatan di era Society 5.0 Guru tidak hanya dituntut memiliki keterampilan teknis dalam menggunakan teknologi, tetapi juga mampu mengolah informasi dengan baik untuk mendukung proses pembelajaran di era Society 5.0. Penelitian ini bertujuan untuk menganalisis secara deskriptif integrasi kecerdasan buatan (Artificial Intelligence/AI) oleh lulusan PPG Prajabatan sebagai upaya mempersiapkan guru profesional di era Society 5.0. Pendekatan yang digunakan dalam penelitian ini adalah metode kuantitatif deskriptif, yaitu dengan mengumpulkan data yang diperoleh dari jawaban responden melalui kuesioner tertutup. Kuesioner yang digunakan terdiri atas 25 pertanyaan dengan menggunakan skala Likert. Hasil kuesioner diolah menggunakan analisis distribusi frekuensi untuk menentukan persentase setiap respons. Subjek penelitian ini berjumlah 98 peserta yang telah menyelesaikan program PPG Prajabatan di beberapa universitas yang tersebar di Indonesia dan telah terakreditasi oleh Kementerian Pendidikan dan Kebudayaan. Hasil penelitian menunjukkan bahwa: (1) calon guru PPG Prajabatan telah mampu menguasai teknologi digital, khususnya dalam mendukung pembelajaran yang mereka laksanakan; (2) calon guru PPG Prajabatan memiliki literasi digital yang baik, terutama untuk mendukung pelaksanaan pembelajaran; (3) calon guru PPG Prajabatan telah melaksanakan pembelajaran berbasis humanisme; (4) calon guru PPG Prajabatan menyadari pentingnya pengembangan diri di era digital saat ini; dan (5) calon guru PPG Prajabatan telah memahami pentingnya evaluasi berbasis data. Selanjutnya, penelitian ini memberikan masukan penting bagi penyelenggara PPG untuk meningkatkan kurikulum yang berkaitan dengan teknologi guna mempersiapkan calon guru dalam menghadapi tuntutan pembelajaran di era Society 5.0.